Multi-level planning : case studies in Mexico - Goreux, Louis M.; Manne, Alan S. (Amsterdam : New York : North-Holland Pub. Co.; American Elsevier Pub. Co., 1973)
This first monograph deals with the problem of interdependence within a single country. It is intended to point the way towards a better understanding of the theory and practice of multi-level planning.
Includes bibliographical references and index.
ne 24/01/2019
Loans
Keywords: Decision making; Policy science; Economic policy - mathematical models; Mexico